(untitled) (Revista Electrónica REDINE, 2021)
The Dissertare Social Science Research Journal began in 2016 with a digital publication of annual periodicity and open access, as an initiative of a group of academics from the Dean of Sciences and Technology of the Lisandro Alvarado Central-Western University of Venezuela (UCLA, in Spanish),interested in opening spaces for the dissemination of socio-humanistic production. Throughout six years of work, Dissertare has entered prestigious international indices, such as Redib, DOAJ, Latindex Catalog 2.0 and ERIH PLUS; furthermore, it has adopted the continuous publication system, increasing its publication frequency from annual to semi-annual. Faced with the growing demands of the digital environment and the social complexities of the current global scenario, Dissertare’s editorial team takes on the challenge of developing new capacities, ratifying the commitment to disseminate social knowledge, including a diversity of approaches and proposals.